Computational Linguistic Models and Language Technologies for Croatian - Dalbelo Bašić, Bojana; Raffaelli, Ida; Tadić, Marko; Dovedan Han, Zdravko; Seljan, Sanja (2007)
This paper gives an overview of the scientific program “ Computational linguistic models and language technologies for Croatian” that has been launched recently. Its short and long term goals, its composition as well as methodology and expected results are presented.
Projekt MZOS
Projekt MZOS
Projekt MZOS
Projekt MZOS
Projekt MZOS
ENG